BOSHLANG‘ICH SINF O’QUVCHILARINING MATEMATIK TAFAKKURINI SHAKLLANTIRISHNING (International conference on multidisciplinary science, 2026)
This  article  examines  the  effectiveness  of  methodological  approaches,  interactive  techniques, logical tasks, problem-based situations, and the use of digital tools in developing the intellectual thinking of primary school students in mathematics education. It also provides a scholarly analysis of the psychological factors influencing the development of mathematical thinking, the innovative forms of organizing learning activities, and the pedagogical competence of the teacher.